Pendampingan Pendidikan Karakter pada Peserta Didik Madrasah Aliyah Nahdlatul Ummah Ponorogo - Murdianto Murdianto; Wahyu Hanafi (Social Science Academic, 2025)
This Community Service activity is part of the Tri Dharma of Higher Education that must be implemented by the academic community, especially those at UNU Yogyakarta. One role that lecturers can play is assisting Islamic educational institutions in developing character education services that are managed programmatically in madrasas and activity implementation units within Islamic boarding schools. The community service implementers chose to strengthen character education, especially at the institution it manages, MA Maarif Nahdlatul Ummah Ponorogo. Madrasah have long implemented character education, and it needs to be strengthened, especially in the aspects of planning and evaluation.